Biomechanics of hip joint: a systematic review - KN, Chethan; Bhat N, Shyamasunder; shenoy B, Satish (International Journal of Engineering and Technology, 2018)
Hip joint is the second largest joint in human after knee joint. It is associated with different types of motion which helps in the movement of human body and provide stability. Biomechanics involves the study of movement of living organism. It is important to know and understand the basics of biomechanics of hip joint to define the movement of hip joint along with its load carrying capacity in different day to day activities. Many researchers are worked to know the basics biomechanics of hip joint both in in-vitro and in- vivo conditions. In this paper, it has been reported in detail to know the different biomechanical aspects involved in the hip joint during different movement and also different biomaterials used in the hip joint prosthesis. It is majorly focused on load transmitting by hip joint by upper body to lower body in different activities such as walking, running, stumbling etc. So, these basic understanding helps to understand effectively the joint reaction forces which is acting on hip joint while designing new hip joint prosthesis.Â Â